Manajemen Kelas sebagai Implementasi Kebijakan dalam Meningkatkan Disiplin dan Partisipasi - Nuraini Ramadhani; Agus Lestari (Administratie: Jurnal Administrasi Publik, 2026)
Classroom management is a crucial element in conducting effective learning in higher education, especially in the context of public administration, which emphasizes the optimal management of educational resources. The background of this research is based on the importance of improving student discipline and participation as indicators of successful learning processes. The aim of the study is to analyze effective classroom management strategies to enhance student discipline and participation through a literature review of various Indonesian scientific journals. The research method uses a systematic literature study with a qualitative approach, identifying and analyzing various classroom management strategies that have been implemented in academic settings. The results show that implementing strategies such as establishing clear classroom rules, active learning methods, positive reinforcement, utilizing educational technology, and managing interpersonal relationships between lecturers and students significantly increase discipline and participation. Internal factors such as student motivation and external factors such as institutional support also influence the effectiveness of these strategies. The impact of this research confirms that well-planned and consistent classroom management not only creates a conducive learning environment, but also contributes to improving the quality of learning and academic performance of university students. These findings can serve as a reference for policymakers and public administration practitioners in designing more effective educational management policies and programs.